Grammar and Inferences of Rationality in Interpreting the Child Pornography Statute - Jeffrey P. Kaplan; Georgia M. Green (Washington University Law Quarterly, 1995)
On November 29, 1994, the U.S. Supreme Court decided United States v. X-Citement Video, Inc., a case which sharply divided participants at the symposium conference. Our discussion here re-constitutes the linguistic analysis which was reduced to a summary in the amicus brief filed by the Law and Linguistics Consortium in that case, and explores the issues which the conclusion of that analysis raised at the symposium.
Keywords: Linguistics; Law – Interpretation & amp; construction; Child pornography